Productive potential of upland rice under conventional and organic farming systems - Gmach, Janice Regina; Coelho, Cileide Maria Medeiros; Parizotto, Círio; Heberle, Isaac; Prezzi, Heitor Amadeu; Mafioleti, André Tesser; Souza, Clovis Arruda; Miquelluti, David José (Comunicata Scientiae, 2018)
This paper aimed to evaluate the genetic diversity of upland rice varieties, determine the components that contributes most to productivity and evaluate the yield of varieties grown in conventional and organic farming systems. The experiment was carried out during the 2011/2012, 2012/2013 and 2013/2014 crop years, with 11 local upland rice varieties (Agulha, Rosa 15, Mato Grosso, Gomes, Preto, Argentino, Kinsel, Camilo, Piriquito, Casca Roxa and Caipira) and two commercial varieties (Primavera and Cambará). Genetic diversity was observed among the varieties for all evaluated variables and the thousand grain weight was the character that contributed most to the divergence between varieties. The number of panicles m-2 was the yield component that presented the highest association with grain yield of varieties in organic farming systems. The average yield of the varieties was 2.303, 1.711 and 3.534 kg ha-1 for the seasons 1, 2 and 3 respectively, and the highest yields were obtained with earlier sowing and temperature during grains maturation about 20°C. The ‘Piriquito’, ‘Argentino’, ‘Gomes’ and ‘Kinsel’ varieties presented yield above 2.000 kg ha-1 for all seasons, in both systems, indicating better adaptation to the region of the study and can be indicated as the most promising for the crop under organic cultivation.